2021
DOI: 10.1016/j.rmed.2021.106602
|View full text |Cite
|
Sign up to set email alerts
|

Complications after discharge with COVID-19 infection and risk factors associated with development of post-COVID pulmonary fibrosis

Abstract: Introduction: Survivors of COVID-19 infection may develop post-covid pulmonary fibrosis (PCF) and suffer from long term multi-system complications. The magnitude and risk factors associated with these are unknown. Objectives: We investigated the prevalence and risk factors associated with PCF and other complications in patients discharged after COVID-19 infection. Methods: Patients had phone assessment 6 weeks post hospital discharge after COVID-19 infection using a set protocol. Those wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 51 publications
3
47
0
1
Order By: Relevance
“…Previous studies have been quite heterogeneous regarding the prevalence of PCPF. Aul et al reported a low prevalence of 9.3% [ 21 ]. Meanwhile, the rest of the available studies have reported a much higher prevalence, ranging from 25.5% to 84.15% [ [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] ], with the highest being reported by Zou and associates [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have been quite heterogeneous regarding the prevalence of PCPF. Aul et al reported a low prevalence of 9.3% [ 21 ]. Meanwhile, the rest of the available studies have reported a much higher prevalence, ranging from 25.5% to 84.15% [ [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] ], with the highest being reported by Zou and associates [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the available literature shared similar findings regarding this aspect [ [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] ]. However, Aul et al reported that the age difference was insignificant between the fibrotic and non-fibrotic patients [ 21 ]. The literature has had contradictory findings regarding the effect of gender and smoking status on the development of fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies analyzed the chest CT characteristics of patients with COVID-19, and patchy ground-glass opacities were the most common changes [7]. The results of further imaging studies for COVID-19 further confirmed that PF might be one of the major complications in patients with COVID-19 [6,10,11].…”
Section: Introductionmentioning
confidence: 94%
“…The disease causes a wide range of symptoms, from asymptomatic to respiratory failure [ 3 , 4 ]. Pulmonary fibrosis (PF) is a possible complication of pulmonary involvement in COVID-19, which is a chronic, progressive, and fatal form of fibrosing interstitial pneumonia [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%